2007
DOI: 10.1258/000456307780945750
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I concentrations in people presenting with diabetic ketoacidosis

Abstract: Minor troponin elevations appear to occur in a small number of subjects with type 1 diabetes presenting with DKA. The clinical relevance of this at this stage remains unknown and further large-scale studies are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In our study, we found that serum level of cTnT I was significantly higher in diabetic children than healthy control that presented an evidence of ongoing myocardial injury caused by uncontrolled DM in these children. Similar results were obtained by other investigators . Interestingly, there was no significant correlation between cTnT I levels and various echocardiographic parameters.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found that serum level of cTnT I was significantly higher in diabetic children than healthy control that presented an evidence of ongoing myocardial injury caused by uncontrolled DM in these children. Similar results were obtained by other investigators . Interestingly, there was no significant correlation between cTnT I levels and various echocardiographic parameters.…”
Section: Discussionsupporting
confidence: 91%
“…These clinical conditions usually cause myocardial necrosis owing to a supply–demand mismatch or direct myocardial toxicity. Diabetic ketoacidosis (DKA) is another condition that can lead to myocardial necrosis in the absence of coronary artery disease (CAD) and has been the subject of previous case reports [1, 2], case series [3], and retrospective reviews [4, 5]. The present case report contributes to the reported data regarding this finding, which has prognostic implications.…”
mentioning
confidence: 60%
“…Our results suggest that a higher methylation level of the TNNT1 gene in high responders compared with low responders could lead to a lower gene transcription rate in those adolescents, allowing them to obtain greater benefits from the weight loss intervention. In regard to the TNNI3 gene, minor troponin I elevations appear to occur in a small number of subjects with type 1 diabetes presenting ketoacidosis (36), but its implication in obesity is still not clear.…”
Section: Discussionmentioning
confidence: 99%